2022
DOI: 10.3390/s22145344
|View full text |Cite
|
Sign up to set email alerts
|

Study on a Detection Technique for Scholte Waves at the Seafloor

Abstract: Scholte waves at the seafloor have significant potential for underwater detection and communication, so a study about detecting Scholte waves is very meaningful in practice. In this paper, the detection of Scholte waves at the seafloor is researched theoretically and experimentally. Acoustic models with the multilayer elastic bottom are established according to the ocean environment, and a tank experiment is designed and carried out to detect Scholte waves. Different from detecting Scholte waves in the seismic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Dispersion phenomenon can be observed when Scholte wave propagates on the seabed, its phase velocity varies with the variation of frequency (Spanos, 2009;Kumar and Saini, 2012;Daniel and Marco, 2019;Chen et al, 2023). In recent years, with the development of marine seismic exploration acquisition equipment, especially the application of efficient seabed surface wave acquisition system with the combination of OBS (Ocean Bottom Seismometer) and air gun source, the Scholte surface wave detection is widely used in seabed engineering geological survey, marine oil and gas exploration and so on (Wu et al, 2021;Qi, 1993;Kugler et al, 2007;Zahra et al, 2016;Krylov et al, 2022a;Liang et al, 2022). The thick sedimentary seabed is usually porous and saturated with seawater in the pores between skeletons which are formed by the long-term deposition and accumulation of granular solid minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion phenomenon can be observed when Scholte wave propagates on the seabed, its phase velocity varies with the variation of frequency (Spanos, 2009;Kumar and Saini, 2012;Daniel and Marco, 2019;Chen et al, 2023). In recent years, with the development of marine seismic exploration acquisition equipment, especially the application of efficient seabed surface wave acquisition system with the combination of OBS (Ocean Bottom Seismometer) and air gun source, the Scholte surface wave detection is widely used in seabed engineering geological survey, marine oil and gas exploration and so on (Wu et al, 2021;Qi, 1993;Kugler et al, 2007;Zahra et al, 2016;Krylov et al, 2022a;Liang et al, 2022). The thick sedimentary seabed is usually porous and saturated with seawater in the pores between skeletons which are formed by the long-term deposition and accumulation of granular solid minerals.…”
Section: Introductionmentioning
confidence: 99%
“…The first work [1] in this volume focuses on seafloor Scholte waves. The authors proposed a method to detect these waves in an acoustic pressure field and found it to be effective even with sediment layers present.…”
mentioning
confidence: 99%